A Participatory Action Research Method in a Rural Community of Mexico - Arellano, Rubi; University of Illinois at Chicago (2016)
For several decades, community interventions have promoted community development with strategies involving capacity building, advocacy, social change, and empowerment. Although community interventions intend to ameliorate social and economic inequalities, there is still a need to evaluate the outcomes of Participatory Action Research (PAR). PAR approaches have demonstrated to be a helpful tool for addressing and identifying community issues and strengths, while leading community members into action. The PAR approach described in this case study of “Ciudad Renace” (Town Reborn)—the Concerns Report Method (CRM)—provided a process for the community to come together and identify main issues, organize, and take actions. The findings suggest multiple activities and outcomes in areas like environmental contamination, social services, and education. Participatory methodologies like the Concerns report Method provided opportunities for community members to become engaged in pursing issues and addressing their own needs. The implications for community psychology research and practice are discussed.